Increased production of IL-17 in children with autism spectrum disorders and co-morbid asthma - Akintunde, Marjannie Eloi (J Neuroimmunol, 2015)
Inflammation and asthma have both been reported in some children with autism spectrum disorder (ASD). To further assess this connection, peripheral immune cells isolated from young children with ASD and typically developing (TD) controls and the production of cytokines IL-17, −13, and −4 assessed following ex vivo mitogen stimulation. Notably, IL-17 production was significantly higher following stimulation in ASD children compared to controls. Moreover, IL-17 was increased in ASD children with co-morbid asthma compared to controls with the same condition. In conclusion, children with ASD exhibited a differential response to T cell stimulation with elevated IL-17 production compared to controls.